Avaliação do efeito tóxico do herbicida trifluralina por meio do estudo histológico e histoquímico do intestino médio do diplópodo Rhinocricus padbergi - Merlini, Vanessa Vanderléia [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Currently the use of pesticides in agriculture is widespread due to their high effectiveness in combating pests, weeds and diseases leading to better productivity and economical performance in agricultural area. The use of pesticides affects the whole world and their use is often performed in an improper and indiscriminate way and for long periods. Several studies have been carried out in order to verify the presence of pesticides in nature, with worrying results. The presence of higher levels of pesticides and their degradation products in soil and surface and groundwater have indicated increasing contamination. Among the most widely used pesticides, herbicides are present and among these trifluralin has occupied an important place due to its widespread use; it is an herbicide originated from benzene derivatives belonging to dinitroanilines family; it is classified as belonging to group C, being possibly carcinogenic for humans, present a high persistence in soil as a result of its low mobility and therefore may affect local edaphic fauna. Diplopods belong to a group of invertebrates considered important in the soil dynamics; due to their close contact with it, these animals can be used as bioindicators of substrates toxicity. This study aimed to expose diplopod specimens of the species R. padbergi to different concentrations of trifluralin and therefore it was mounted five bioassays containing soil from the site where animals were collected (control group) and the same soil mixed to different concentrations of trifluralin herbicide (concentration recommended for agriculture use, that is, the dose recommended by the producer 0.0534g/m2, double, haft and quarter of this dose), animals were exposed for 7 and 90 days. During the entire period of exposure (90 days), it was observed that the number of animals in the control bioassay remained stable until the 5th week, presenting only... (Complete abstract click electronic access below)

Atualmente, o uso de agrotóxicos na agricultura é muito disseminado pela grande eficácia no combate a pragas, ervas daninhas e doenças, contribuindo para uma melhor produtividade e rendimento econômico na área agrícola. O uso de agroquímicos atinge o mundo todo e muitas vezes a sua utilização é feita de modo abusivo, indiscriminado e por longos períodos. Várias pesquisas vêm sendo realizadas no intuito de verificar a presença de agrotóxicos na natureza, com resultados preocupantes. A presença de níveis altíssimos de agroquímicos e seus produtos de degradação em solos e águas superficiais e subterrâneas vêm indicando contaminações cada vez maiores. Dentre os agroquímicos mais utilizados, estão presentes os herbicidas e dentre estes a trifluralina tem ocupado um lugar relevante devido ao seu amplo uso; é um herbicida proveniente de derivados benzênicos pertencentes à família da dinitroanilina; é classificada como pertencente ao grupo C, sendo possivelmente carcinogênico em humanos, possui alta persistência no solo como conseqüência da sua baixa mobilidade, podendo desta maneira afetar a fauna edáfica local. Os diplópodos compreendem um grupo de invertebrados importantes na dinâmica do solo; por possuirem um íntimo contato com o mesmo, estes animais podem ser utilizados como bioindicadores na toxicidade de substratos. O presente trabalho objetivou por expor espécimes de diplópodos da espécie R. padbergi, a diferentes concentrações de trifluralina desta forma, foram montados cinco bioensaios contendo terra proveniente do local de coleta dos animais (grupo controle) e a mesma terra misturada ao herbicida trifluralina em diferentes concentrações (concentração indicada para uso agrícola, sendo a dose recomendada pelo fabricante de 0,0534 g/m2, o dobro, a metade e um quarto desta dose), os animais foram expostos por 7 e 90 dias... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Produtos químicos agrícolas; Herbicidas; Milipede - Aparelho digestivo; Toxicologia; Histopatologia